Impact of storage on variations in volatiles, essential phytonutrients and minerals in aggregatum Onion (Bangladesh Journal of Botany, 2025)
This study was carried out from 2020 to 2023 at Anbil Dharmalingam Agricultural College & Research Institute (Tamil Nadu Agricultural University), Tiruchirappalli, Tamil Nadu, India, with the indigenous aggregatum variety. Growers in southern India, particularly in Tamil Nadu, traditionally store aggregatum onions in conventional storage structures for up to 6 months. During the 30-day preservation period, certain phytonutrients were examined. Quercetin is an important phytonutrient that decreases after 30 days of storage, dropping from 11.1 to 1.11 mg/kg. Similarly, selenium levels decreased from 150.6 to 80.04 µg/g. Additionally, GCMS/MS was used to evaluate the metabolites during the initial and 30-day storage periods. Beneficial metabolites were dramatically reduced, with 17 different metabolites lowered after 30 days of storage. This study focuses on the loss of essential phytonutrients during the storage of aggregatum onions in typical storage structures, which has tremendous impacts on their quality.Bangladesh J. Bot. 54(2): 403-407, 2025 (June)